The effect of omega 3 fatty acid supplementation on premenstrual syndrome and health-related quality of life: a randomized clinical trial - Samira Behboudi-Gandevani; Fatemeh-Zahra Hariri; Lida Moghaddam-Banaem (Taylor & Francis Group, 2018)
Introduction: Most reproductive aged women suffer from somatic and mental disorders prior to menstruation. This study investigated whether omega-3 supplement improved premenstrual symptoms and health-related quality of life among reproductive aged women. Methods: A multi-center, balanced (1:1), placebo-controlled, parallel-group randomized clinical trial was conducted in an urban academic institution. A sample consisting of 95 Iranian women aged 20-35 years who were suffering from premenstrual symptoms were randomly allocated into two groups. The treatment consisted of omega-3 supplement containing 1 g fish oil. Placebo was free of oil. The premenstrual symptoms' screening tool and 12-item short form health survey questionnaire were used for data collection. Results: No statistically significant differences in the baseline characteristics of the groups were reported. Most premenstrual symptoms and their interference with daily activities were significantly reduced over the follow-up period. The mean score of overeating in the omega-3 supplement group and insomnia in the placebo group showed no difference between the groups. The longer use of omega-3 supplement provides improvement of premenstrual symptoms and activities. The mean scores of physical and mental components of quality of life were significantly improved in the omega-3 supplement and placebo groups. Discussion: The treatment of premenstrual symptoms using omega-3 supplement reduced symptoms and ameliorated women's quality of life.